Solid electrolyte membrane, preparation method thereof and all-solid-state battery

By forming a lithium-conducting support network in the solid electrolyte membrane and filling the modified sulfide solid electrolyte, the problems of environmental adaptability and cost of sulfide solid electrolyte in the prior art are solved, and high ionic conductivity, mechanical properties and stability are achieved The solid electrolyte membrane improves the performance of solid-state batteries.

CN119447424APending Publication Date: 2025-02-14XIAMEN BAOLONG NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594539.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing sulfide solid electrolyte has poor environmental adaptability and high cost, while the polymer solid electrolyte has poor ionic properties and good strength, which makes it easy to deposit films, making it difficult to prepare high-performance solid electrolyte membranes.

Method used

The polymer solid electrolytes are crosslinked to form a lithium-conducting support network, and the modified sulfide solid electrolyte is filled between the lithium-conducting support networks. The modified sulfide solid electrolyte is modified by grafting of thiodecafluorooctyletriethoxysilane improves interface compatibility and stability.

Benefits of technology

Improves the ionic conductivity, mechanical properties and stability of the solid electrolyte membrane, so that it can withstand higher operating pressure, buffers the volume expansion and contraction during charging and discharging, and improves the cycle stability, safety and electrical power of the solid battery. Chemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126484450000071
    Figure BDA0005126484450000071
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a solid electrolyte membrane, a preparation method thereof and an all-solid-state battery. The preparation method of the solid electrolyte membrane comprises the following steps: S1, dissolving a polymer solid electrolyte in a solvent with a low melting point in parts by mass, then adding a modified sulfide solid electrolyte, uniformly stirring, and defoaming to prepare solid electrolyte slurry; and S2, coating the surface of a PET release film with the solid electrolyte slurry, drying in vacuum at 110 DEG C after airing, and then removing the PET release film to obtain the solid electrolyte film with the thickness of 20 microns. According to the preparation method of the solid-state electrolyte membrane, the performance indexes, including energy density, safety and electrochemical performance, of the battery are improved, some key challenges faced by a traditional solid-state electrolyte membrane are solved through innovative design of materials and structures, and a powerful technical support is provided for development and application of a high-performance solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a solid electrolyte membrane and a preparation method thereof and an all-solid-state battery. Background Art

[0002] As the demand for lithium-ion batteries in electric vehicles, smart phones, power storage and other fields continues to grow, the energy density and safety performance of batteries have become two major focuses of consumer attention.

[0003] All-solid-state batteries use solid electrolytes and do not contain flammable and explosive organic solvents. They can fundamentally solve the negative problems caused by electrolytes, improve battery safety performance, and make the use of higher energy density battery systems possible.

[0004] As the core component of solid-state batteries, the properties of solid electrolyte membranes restrict the performance of batteries. Sulfide system electrolytes have high conductivity and strong processability, and are one of the most promising solid-state solutions. However, sulfides currently have poor environmental adaptability and high costs, while polymer solid electrolytes have poor ionicity, but they are strong and easy to deposit. Therefore, a high-performance solid electrolyte membrane is prepared by taking advantage of the good conductivity of sulfides and the weak conductivity of polymer solid electrolytes, but with strong deposition performance and good toughness. Summary of the invention

[0005] In order to solve the above problems, the present application provides a solid electrolyte membrane and a preparation method thereof and an all-solid-state battery. The solid electrolyte membrane prepared by the present application has thin thickness, high mechanical strength, wide window, rigidity and flexibility, high ion conductivity, and improves the safety and cycle performance of the battery. The present application uses polymer solid electrolytes to cross-link with each other to form a lithium-conducting support network, and the modified sulfide solid electrolyte is filled between the lithium-conducting support networks. The formation of the lithium-conducting support network can effectively conduct lithium ions, shorten the transmission distance of lithium ions, reduce the transfer impedance between electrolyte particles, and improve ion conductivity. The solid electrolyte membrane can withstand higher operating pressures, improve the stability of the solid electrolyte membrane, and enable it to buffer the volume expansion and contraction during charging and discharging, effectively improving the cycle stability, safety and electrochemical performance of the solid-state battery. Among them, by grafting coupling agents on the surface of sulfide solid electrolytes, the interfacial compatibility between polymer solid electrolytes and sulfide solid electrolyte particles is improved, so that high-content sulfide particles are evenly distributed in the polymer matrix; the ability of the surface of sulfide solid electrolyte particles to resist water and oxygen is improved, so that the sulfide particles have higher air stability; the interaction between polymer solid electrolytes and sulfide solid electrolyte particles is improved, and the prepared solid electrolyte membrane has good mechanical properties.

[0006] In a first aspect, the present application provides a method for preparing a solid electrolyte membrane, using the following technical solution: A method for preparing a solid electrolyte membrane comprises the following steps: S1. Dissolve the polymer solid electrolyte in a solvent with a low melting point according to the mass fraction, then add the modified sulfide solid electrolyte, stir evenly, and degas to obtain a solid electrolyte slurry; S2. The solid electrolyte slurry is coated on the surface of the PET release film, dried in a vacuum oven at 110° C. for 12-24 hours, and then the PET release film is removed to obtain a solid electrolyte membrane with a thickness of 20 μm.

[0007] By adopting the above technical scheme, S1 (preparation of solid electrolyte slurry): This step is the basis of the entire preparation process. The polymer solid electrolyte is dissolved in a solvent with a low melting point, and then the modified sulfide solid electrolyte is added and stirred evenly to form a uniform slurry. The degassing operation ensures that there are no bubbles in the material, which is crucial for the subsequent coating process and the quality of the final film. This step lays the foundation for the formation of a uniform and defect-free electrolyte membrane. S2 (coating and drying): The solid electrolyte slurry is coated on the PET release film, and the solvent is removed by drying and vacuum drying. This step is the key to forming a solid electrolyte membrane. These operations together ensure that the electrolyte membrane has the required thickness, uniformity and mechanical stability. Modified sulfide solid electrolyte: provides high ionic conductivity and is the main medium for lithium ion conduction. Modification improves its dispersibility and interfacial compatibility in the polymer matrix and reduces the transfer impedance between particles. Polymer solid electrolyte: forms a lithium-conducting support network, which enhances the mechanical properties and stability of the electrolyte membrane. The presence of the polymer not only improves the flexibility of the material, but also helps to buffer the volume change during charge and discharge, thereby improving the safety and cycle life of the battery. Overall, this application achieves high ionic conductivity, good mechanical properties and stability, and excellent electrochemical performance of the solid electrolyte membrane through carefully designed material selection and process steps. These characteristics make the solid electrolyte membrane very suitable for use in high-performance solid-state batteries, especially in improving the energy density and safety of the battery.

[0008] Preferably, in step S1, the mass ratio of the modified sulfide solid electrolyte to the polymer solid electrolyte is (90-95):(5-10).

[0009] Preferably, in step S1, the preparation method of the modified sulfide solid electrolyte is: adding tridecafluorooctyltriethoxysilane, sulfide solid electrolyte and anhydrous acetonitrile into a reactor, reacting for 8 hours at 80°C in a nitrogen atmosphere, then centrifuging, collecting the solid, washing the solid three times with anhydrous acetonitrile, and drying under vacuum at 50°C for 12 hours to obtain a modified sulfide solid electrolyte.

[0010] By adopting the above technical scheme, the prepared modified sulfide solid electrolyte has the following effects and synergistic effects: Improved interfacial compatibility: By grafting the surface of the sulfide solid electrolyte with tridecafluorooctyl triethoxysilane, the interfacial compatibility between the polymer solid electrolyte and the sulfide solid electrolyte particles can be significantly improved. This improved compatibility helps the sulfide particles to be more evenly distributed in the polymer matrix, thereby improving the overall performance of the solid electrolyte membrane. Enhanced stability and environmental resistance: The surface of the modified sulfide solid electrolyte particles has better resistance to water and oxygen, which means that their stability in the air is improved, reducing the performance degradation that may be caused by environmental factors during battery operation. Optimized mechanical properties: By modifying the interaction between the sulfide solid electrolyte and the polymer solid electrolyte, a solid electrolyte membrane with good mechanical properties can be prepared. This membrane can withstand higher operating pressures and can effectively buffer volume expansion and contraction during charging and discharging, thereby effectively improving the cycle stability, safety and electrochemical performance of solid-state batteries. Improve ion conductivity: The modified sulfide solid electrolyte is filled between the lithium-conducting support network formed by the ion-conducting polymer. Such a structural design helps to shorten the transmission distance of lithium ions and reduce the transfer impedance between electrolyte particles, thereby improving the ion conductivity. This is crucial to improving the charge and discharge efficiency and cycle stability of the battery. Synergy: The combination of modified sulfide solid electrolyte and polymer solid electrolyte not only plays their respective advantages, but also produces a synergistic effect. The polymer provides flexibility and processability, while the modified sulfide contributes high ionic conductivity and good thermal stability. This combination makes the final solid electrolyte membrane have both excellent physical properties and high ion conductivity.

[0011] Preferably, the usage ratio of the sulfide solid electrolyte, tridecafluorooctyltriethoxysilane and anhydrous acetonitrile is 100g:(2g-4g):0.6L.

[0012] Preferably, the sulfide solid electrolyte is Li 6 PS 5 Cl, Li 6 PS 5 Br and Li 10 SnP 2 S 12 At least one of the sulfide solid electrolytes has a D50 of 3-5 μm.

[0013] Preferably, the polymer solid electrolyte is composed of polyethylene oxide and an ion-conducting polymer in a mass ratio of 1:3.

[0014] By adopting the above technical scheme, the polymer solid electrolyte is composed of polyethylene oxide (PEO) and ion conductive polymer in a mass ratio of 1:3. This combination makes full use of the characteristics of the two materials to achieve high performance of the solid electrolyte membrane. Polyethylene oxide (PEO) is a commonly used polymer matrix material with good mechanical properties and chemical stability. As a polymer matrix, PEO provides good structural support and stability for the solid electrolyte membrane. At the same time, PEO also has a certain ion conductivity, which can improve the ion conductivity of the solid electrolyte membrane to a certain extent. Ion conductive polymer is a special polymer with high ion conductivity and good chemical stability. The ion conductive polymer and PEO are cross-linked to form a lithium conductive support network. This network structure helps the transmission of lithium ions, shortens the transmission distance of lithium ions, and reduces the transfer impedance between electrolyte particles, thereby improving the ion conductivity of the solid electrolyte membrane. In addition, the ion conductive polymer also has high mechanical strength, which can improve the compressive strength of the solid electrolyte membrane, enabling it to withstand higher operating pressure.

[0015] Preferably, the method for preparing the ion-conducting polymer comprises the following steps: S71, weighing styrene sulfonic acid and lithium hydroxide in a molar ratio of 1:1, respectively dissolving them in deionized water to obtain an 8 wt % styrene sulfonic acid aqueous solution and an 8 wt % lithium hydroxide aqueous solution, respectively, adding the lithium hydroxide aqueous solution dropwise to the styrene sulfonic acid aqueous solution, fully neutralizing the reaction, drying to remove water, and obtaining lithium p-styrene sulfonate; S72. Weigh lithium p-styrene sulfonate, styrene and azobisisobutyronitrile in a molar ratio of 1:1:0.005 respectively, dissolve lithium p-styrene sulfonate and styrene in N,N-dimethylformamide, add azobisisobutyronitrile, and thermally polymerize at 65°C for 6 hours. Purify by recrystallization with methanol and ethyl ether to obtain an ion-conducting polymer.

[0016] By adopting the above technical scheme, an ion-conducting polymer is prepared, and the ion-conducting polymer is cross-linked to form a lithium-conducting support network. The modified sulfide solid electrolyte is filled between the lithium-conducting support networks. The formation of the lithium-conducting support network can effectively conduct lithium ions, shorten the transmission distance of lithium ions, reduce the transfer impedance between electrolyte particles, and improve the ion conductivity. The solid electrolyte membrane can withstand higher operating pressures, improve the stability of the solid electrolyte membrane, enable it to buffer the volume expansion and contraction during charging and discharging, and effectively improve the cycle stability, safety and electrochemical performance of the solid-state battery.

[0017] Preferably, in step S1, the solvent with a low melting point is at least one of acetone, isopropanol and tetrahydrofuran.

[0018] In a second aspect, the present application provides a solid electrolyte membrane, which adopts the following technical solution: As a general technical concept, the present application also provides a solid electrolyte membrane, which is prepared by the above-mentioned method for preparing the solid electrolyte membrane, and the ionic conductivity of the solid electrolyte membrane is ≥1.5mS / cm.

[0019] In a third aspect, the present application provides an all-solid-state battery, which adopts the following technical solution: As a general technical concept, the present application also provides an all-solid-state battery, including the above-mentioned solid-state electrolyte membrane.

[0020] In summary, the beneficial technical effects of this application are: 1. Improve ion conductivity: By cross-linking polymer solid electrolytes to form a lithium-conducting support network, and filling the modified sulfide solid electrolyte between the lithium-conducting support networks, lithium ions are effectively conducted, the transmission distance of lithium ions is shortened, and the transmission impedance between electrolyte particles is reduced.

[0021] 2. Enhanced mechanical properties: By grafting tridecafluorooctyltriethoxysilane on the surface of the sulfide solid electrolyte, the interfacial compatibility between the polymer solid electrolyte and the sulfide solid electrolyte particles is improved, so that the high-content sulfide particles are evenly distributed in the polymer matrix, thereby enhancing the mechanical properties of the solid electrolyte membrane.

[0022] 3. Improve stability and safety: The solid electrolyte membrane can withstand higher operating pressure, which improves its stability and enables it to buffer the volume expansion and contraction during charging and discharging, effectively improving the safety of solid-state batteries.

[0023] 4. Improve electrochemical performance: The application of modified sulfide solid electrolytes improves the interaction between polymer solid electrolytes and sulfide solid electrolyte particles, which is beneficial to improving the energy density and electrochemical performance of solid-state batteries.

[0024] 5. Environmental stability: The ability of the surface of the modified sulfide solid electrolyte particles to resist water and oxygen is improved, so that the sulfide particles have higher air stability, which is beneficial for the long-term storage and use of the battery.

[0025] 6. Thinning: The thickness of the obtained solid electrolyte membrane is only 20 microns, which helps to further reduce the overall size of the battery and is of great significance for improving the volume energy density and portability of the battery. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] In the following examples, 1 part means 100 g, and the weight average molecular weight of polyethylene oxide is 150W.

[0028] Preparation Example 1 Preparation of ion-conducting polymer The method for preparing an ion-conducting polymer comprises the following steps: S71, weighing styrene sulfonic acid and lithium hydroxide in a molar ratio of 1:1, respectively dissolving them in deionized water to obtain an 8 wt % styrene sulfonic acid aqueous solution and an 8 wt % lithium hydroxide aqueous solution, respectively, adding the lithium hydroxide aqueous solution dropwise to the styrene sulfonic acid aqueous solution, fully neutralizing the reaction, drying to remove water, and obtaining lithium p-styrene sulfonate; S72. Weigh lithium p-styrene sulfonate, styrene and azobisisobutyronitrile in a molar ratio of 1:1:0.005 respectively, dissolve lithium p-styrene sulfonate and styrene in N,N-dimethylformamide, add azobisisobutyronitrile (the amount of azobisisobutyronitrile added is 2% of the mass of lithium p-styrene sulfonate), thermally polymerize at 65°C for 6h, and purify by recrystallization method using methanol and ethyl ether to obtain an ion-conducting polymer.

[0029] Example 1 A method for preparing a solid electrolyte membrane comprises the following steps: S1. According to the mass fraction, 10 parts of polymer solid electrolyte are dissolved in 800 parts of acetone, and then 90 parts of modified sulfide solid electrolyte are added, stirred evenly, and degassed to obtain a solid electrolyte slurry; the polymer solid electrolyte is composed of polyethylene oxide and ion conductive polymer in a mass fraction ratio of 1:3; the preparation method of the modified sulfide solid electrolyte is: 2g of tridecafluorooctyl triethoxysilane, 100g of Li 6 PS 5 Cl powder and 0.6L anhydrous acetonitrile were added into the reactor, reacted at 80°C in a nitrogen atmosphere for 8 hours, then centrifuged to collect the solid, washed the solid three times with anhydrous acetonitrile, and dried at 50°C in vacuum for 12 hours to obtain a modified sulfide solid electrolyte; S2. The solid electrolyte slurry is coated on the surface of the PET release film, dried in a vacuum oven at 110° C. for 12 hours, and then the PET release film is removed to obtain a solid electrolyte membrane with a thickness of 20 μm.

[0030] Example 2 A method for preparing a solid electrolyte membrane comprises the following steps: S1. Dissolve 5 parts of polymer solid electrolyte in 800 parts of isopropanol according to mass fractions, then add 95 parts of modified sulfide solid electrolyte, stir evenly, degas, and prepare solid electrolyte slurry; the polymer solid electrolyte is composed of polyethylene oxide and ion conductive polymer in a mass fraction ratio of 1:3; the preparation method of the modified sulfide solid electrolyte is: 4g of tridecafluorooctyl triethoxysilane, 100g of Li 6 PS 5 Br powder and 0.6L anhydrous acetonitrile were added into the reactor, reacted at 80°C in a nitrogen atmosphere for 8 hours, then centrifuged to collect the solid, washed the solid three times with anhydrous acetonitrile, and dried at 50°C in vacuum for 12 hours to obtain a modified sulfide solid electrolyte; S2. The solid electrolyte slurry is coated on the surface of the PET release film, dried in a vacuum oven at 110° C. for 24 hours, and then the PET release film is removed to obtain a solid electrolyte membrane with a thickness of 20 μm.

[0031] Example 3 A method for preparing a solid electrolyte membrane comprises the following steps: S1. According to the mass fraction, 7 parts of polymer solid electrolyte are dissolved in 800 parts of tetrahydrofuran, and then 93 parts of modified sulfide solid electrolyte are added, stirred evenly, and degassed to obtain a solid electrolyte slurry; the polymer solid electrolyte is composed of polyethylene oxide and ion conductive polymer in a mass fraction ratio of 1:3; the preparation method of the modified sulfide solid electrolyte is: 3g of tridecafluorooctyl triethoxysilane, 100g of Li 10 SnP 2 S 12 The powder and 0.6L of anhydrous acetonitrile were added into a reactor, reacted at 80°C in a nitrogen atmosphere for 8 hours, and then centrifuged to collect the solid, washed the solid three times with anhydrous acetonitrile, and dried at 50°C in vacuum for 12 hours to obtain a modified sulfide solid electrolyte; S2. The solid electrolyte slurry is coated on the surface of the PET release film, dried in a vacuum oven at 110° C. for 16 hours, and then the PET release film is removed to obtain a solid electrolyte membrane with a thickness of 20 μm.

[0032] Comparative Example 1 The same as Example 3, except that: the polymer solid electrolyte is polyethylene oxide.

[0033] Comparative Example 2 The same as Example 3, except that: the polymer solid electrolyte is an ion-conducting polymer.

[0034] Comparative Example 3 Same as Example 3, except that an equal amount of Li with a D50 of 4 μm is used. 10 SnP 2 S 12 Powder replaces modified sulfide solid electrolyte.

[0035] Performance Testing The solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were sampled and tested respectively. The test results are shown in Table 1.

[0036] Ionic conductivity test: The AC impedance test was conducted using a Transmission Power 1260A impedance / gain-phase analyzer with a frequency range of 1mHz-0.1Hz. The solid electrolyte membrane was cut into discs with a diameter of 10mm, and carbon-coated aluminum foil was attached on both sides. It was placed in a mold battery PEEK sleeve, and then stainless steel columns were inserted on both sides to block the electrodes. The test was conducted under a pressure of 360MPa, and the ionic conductivity of the solid electrolyte membrane was calculated; Mechanical properties: The solid electrolyte membrane was cut into small discs with a diameter of 10 mm, bent 180° and 180° in the opposite direction, and its mechanical damage (including cracks, fractures, creases, etc.) was observed.

[0037] All-solid-state battery assembly: In an inert gas glove box with a water and oxygen content of ≤0.01ppm, the solid electrolyte membrane and the positive and negative electrodes are assembled together. The positive electrode has a NCM811 loading of 10mg cm per unit area. -2 The electrode is made of lithium metal as the negative electrode layer and the adhesive is PVDF, which is assembled into an all-solid-state battery. Finally, the first efficiency is tested by cyclic discharge at 0.1C, and the capacity retention rate is tested after 50 cycles.

[0038] Table 1 Electrochemical performance test results Analyzing the data in Table 1, we can see that: 1) The solid electrolyte membranes prepared in Examples 1 to 3 have thin thickness, high mechanical strength, both rigidity and flexibility, and high ionic conductivity, thereby improving the safety and cycle performance of the battery.

[0039] 2) The performance comparison analysis of the solid electrolyte membranes prepared in combination with Example 3 and Comparative Examples 1-2 shows that the polymer solid electrolyte is composed of polyethylene oxide and ion-conducting polymer in a mass ratio of 1:3. By utilizing the synergistic effect between them, the ion-conducting polymer and polyethylene oxide are cross-linked to form a lithium-conducting support network. This network structure helps the transmission of lithium ions, shortens the transmission distance of lithium ions, and reduces the transfer impedance between electrolyte particles, thereby improving the ion conductivity of the solid electrolyte membrane. In addition, the ion-conducting polymer also has a high mechanical strength, which can improve the compressive strength of the solid electrolyte membrane, so that it can withstand higher operating pressures.

[0040] 3) The performance comparison analysis of the solid electrolyte membrane prepared in combination with Example 3 and Comparative Example 3 shows that the modified sulfide solid electrolyte prepared in the present application is grafted and modified on the surface of the sulfide solid electrolyte by tridecafluorooctyl triethoxysilane, which can significantly improve the interfacial compatibility between the polymer solid electrolyte and the sulfide solid electrolyte particles. This improved compatibility helps the sulfide particles to be more evenly distributed in the polymer matrix, thereby improving the overall performance of the solid electrolyte membrane. The surface of the modified sulfide solid electrolyte particles has better resistance to water and oxygen, which means that their stability in the air is improved, reducing the performance degradation that may be caused by environmental factors during the operation of the battery. Through the interaction between the modified sulfide solid electrolyte and the polymer solid electrolyte, a solid electrolyte membrane with good mechanical properties can be prepared. This membrane can withstand higher operating pressures and can effectively buffer volume expansion and contraction during charge and discharge, thereby effectively improving the cycle stability, safety and electrochemical performance of the solid-state battery. The modified sulfide solid electrolyte is filled between the lithium-conducting support network formed by the ion-conducting polymer. This structural design helps to shorten the transmission distance of lithium ions and reduce the transfer impedance between electrolyte particles, thereby improving ion conductivity. This is crucial to improving the charge and discharge efficiency and cycle stability of the battery.

[0041] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a solid electrolyte membrane, characterized in that: The following steps are involved: S1. Dissolve the polymer solid electrolyte in a solvent with a low melting point according to the mass fraction, then add the modified sulfide solid electrolyte, stir evenly, and degas to obtain a solid electrolyte slurry; S2. The solid electrolyte slurry is coated on the surface of the PET release film, dried in a vacuum oven at 110° C. for 12-24 hours, and then the PET release film is removed to obtain a solid electrolyte membrane with a thickness of 20 μm.

2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S1, the mass ratio of the modified sulfide solid electrolyte to the polymer solid electrolyte is (90-95):(5-10).

3. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S1, the preparation method of the modified sulfide solid electrolyte is: add tridecafluorooctyltriethoxysilane, sulfide solid electrolyte and anhydrous acetonitrile into a reactor, react for 8 hours at 80°C in a nitrogen atmosphere, then centrifuge to collect the solid, wash the solid three times with anhydrous acetonitrile, and dry it at 50°C in vacuum for 12 hours to obtain a modified sulfide solid electrolyte.

4. The method for preparing a solid electrolyte membrane according to claim 3, characterized in that: The usage ratio of the sulfide solid electrolyte, tridecafluorooctyltriethoxysilane and anhydrous acetonitrile is 100g: (2g-4g): 0.6L.

5. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The sulfide solid electrolyte is Li6PS5Cl, Li6PS5Br and Li 10 SnP2S 12 At least one of the sulfide solid electrolytes has a D50 of 3-5 μm.

6. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S1, the polymer solid electrolyte is composed of polyethylene oxide and an ion-conducting polymer in a mass ratio of 1:

3.

7. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: The method for preparing the ion-conducting polymer comprises the following steps: S71, weighing styrene sulfonic acid and lithium hydroxide in a molar ratio of 1:1, respectively dissolving them in deionized water to obtain an 8 wt % styrene sulfonic acid aqueous solution and an 8 wt % lithium hydroxide aqueous solution, respectively, adding the lithium hydroxide aqueous solution dropwise to the styrene sulfonic acid aqueous solution, fully neutralizing the reaction, drying to remove water, and obtaining lithium p-styrene sulfonate; S72. Weigh lithium p-styrene sulfonate, styrene and azobisisobutyronitrile in a molar ratio of 1:1:0.005 respectively, dissolve lithium p-styrene sulfonate and styrene in N,N-dimethylformamide, add azobisisobutyronitrile, and thermally polymerize at 65°C for 6 hours. Purify by recrystallization with methanol and ethyl ether to obtain an ion-conducting polymer.

8. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step S1, the solvent with a low melting point is at least one of acetone, isopropanol and tetrahydrofuran.

9. A solid electrolyte membrane prepared according to the method for preparing a solid electrolyte membrane according to any one of claims 1 to 8, characterized in that: The ionic conductivity of the solid electrolyte membrane is ≥1.5 mS / cm.

10. An all-solid-state battery, characterized in that: Comprising the solid electrolyte membrane according to claim 9.